PEMBUATAN BIOPESTISIDA DAN PUPUK ORGANIK DARI LIMBAHSAYURAN - Aidha Trisanty (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Kayuares, Bandung Rejo village, District Ngablak, Magelang, Central Java.Mostly livelihood society is a farmer,breeder, and laborers. Kayuares society have aminimal standard of living, caused by low public education. This causes children to theDusun Kayuares lack of parental guidance and lack of time parents to teach theirchildren. Kayuares society also has problems in agriculture are fertilizers and pesticidesare expensive so bad effect on the environment and surrounding communities, whereasthese pesticides fertilizer can be made by citizens with abundant raw materials from thewaste products of the earth. To resolve this issue held beopestisida and manufactureorganic fertilizer so as to drive the community.